One Hundred Mitochondrial Genomes of Cicadas. (22nd December 2018) - Łukasik, Piotr; Chong, Rebecca A; Nazario, Katherine; Matsuura, Yu; Bublitz, De Anna C; Campbell, Matthew A; Meyer, Mariah C; Van Leuven, James T; Pessacq, Pablo; Veloso, Claudio; Simon, Chris; McCutcheon, John P
Abstract: Mitochondrial genomes can provide valuable information on the biology and evolutionary histories of their host organisms. Here, we present and characterize the complete coding regions of 107 mitochondrial genomes (mitogenomes) of cicadas (Insecta: Hemiptera: Auchenorrhyncha: Cicadoidea), representing 31 genera, 61 species, and 83 populations. We show that all cicada mitogenomes retain the organization and gene contents thought to be ancestral in insects, with some variability among cicada clades in the length of a region between the genes nad2 and cox1, which encodes 3 tRNAs. Phylogenetic analyses using these mitogenomes recapitulate a recent 5-gene classification of cicadas into families and subfamilies, but also identify a species that falls outside of the established taxonomic framework. While protein-coding genes are under strong purifying selection, tests of relative evolutionary rates reveal significant variation in evolutionary rates across taxa, highlighting the dynamic nature of mitochondrial genome evolution in cicadas. These data will serve as a useful reference for future research into the systematics, ecology, and evolution of the superfamily Cicadoidea.